Delamination Fracture Analyses of Linear-Elastic Functionally Graded Beams - RIZOV, Victor Iliev (Engineering Transactions, 2017)
An analytical approach for investigation of delamination cracks in three-dimensional functionally graded linear-elastic beams was developed. Beams which are functionally graded along their width, height and length were analyzed. The fracture was studied in terms of the strain energy release rate. Beams loaded by a combination of bending moments and an axial force were considered. The approach was applied to determine the strain energy release rate for a delamination crack in a functionally graded beam of rectangular cross-section loaded in eccentric tension. An additional analysis was performed by using the beam strain energy for verification. The effects of material gradient and crack length on the delamination were evaluated.